PENGARUH HARGA MINYAK DUNIA TERHADAP PERTUMBUHAN EKONOMI, INFLASI, DAN PENGANGGURAN DI INDONESIA - Sodik Dwi Purnomo; Istiqomah; Lilis Siti Badriah (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2020)
The purpose of this research is to analyze the influence of oil prices fluctuations to Indonesia macroeconomics that is economic growth, inflation, and unemployment from 1988 to 2018. The data analysis technique uses Vector Autoregressive (VAR) with Eviews for windows application. The result showed that oil price fluctuations in the amount of one standard deviation will gives a positive influence to economic growth, inflation rate, and unemployment which each has 0,001 percent, 0,001 percent, and 0,002 percent